Saponin seed priming improves salt tolerance in quinoa. (1st August 2017) - Yang, A.; Akhtar, S. S.; Iqbal, S.; Qi, Z.; Alandia, G.; Saddiq, M. S.; Jacobsen, S.‐E.
Abstract: Quinoa ( Chenopodium quinoa Willd.) is a facultative halophyte of great value, and World Health Organization has selected this crop, which may assure future food and nutritional security under changing climate scenarios. However, germination is the main critical stage of quinoa plant phenology affected by salinity. Therefore, two experiments were conducted to improve its performance under salinity by use of saponin seed priming. Seeds of cv. Titicaca were primed in seven different solutions with varying saponin concentrations (i.e. 0%, 0.5%, 2%, 5%, 10%, 15%, 25% and 35%), and then, performances of primed seeds were evaluated based on mean germination time and final germination percentage in germination assays (0 and 400 mM NaCl stress). Saponin solutions of 10%, 15% and 25% concentration were found most effective priming tools for alleviating adverse effects of salt stress during seed germination. Performances of these primed seeds were further evaluated in pot study. At six‐leaf stage, plants were irrigated with saline water having either 0 or 400 mM NaCl. The results indicated that saline irrigation significantly decreased the growth, physiology and yield of quinoa, whereas saponin priming found operative in mitigating the negative effects of salt stress. Improved growth, physiology and yield performance were linked with low ABA concentration, better plant water (osmotic and water potential) and gas relations (leaf photosynthetic rate, stomatal conductance), low Na + and high K + contents in leaves. Our results suggest that saponin priming could be used as an easy‐operated and cost‐effective technology for sustaining quinoa crop growth on salt‐affected soils.